Czechoslovakia and Eastern Europe in the Era of Normalisation, 1969–1989
XIX, 345 p. 3 illus.
Keywords: “The post-1968 ‘normalisation’ era in Czechoslovakia is usually dismissed as ‘grey’, yet, until Gorbachev, it represented the Soviet-sanctioned archetype for ‘real socialism’. This superb collection, with its unprecedented range of analysis and themes, disperses the grey to reveal vibrant complexity and in so doing fills a real gap in the historiography." —Nigel Swain, Lecturer, University of Liverpool, UK This edited collection represents the first comprehensive volume in English on the crucial, but under-explored, late period in the history of East European communism. Focusing on developments in Czechoslovakia from the crushing of the Prague Spring in August 1968 to the ‘Velvet Revolution’ of November 1989, the book examines a broad range of political, social and cultural issues, while also analysing external perceptions and relations. It explores the concept of ‘normalisation’ in historical context and brings together British, American, Czech and Slovak experts, each with their own archival research and particular interpretations. Overall, the anthology aims to assess the means by which the Prague Spring reforms were repealed and how Czechoslovakia was returned to a ‘normal’ communist state in line with Soviet orthodoxy. Key themes include the Communist Party and ideology; State Security; Slovak developments; ‘auto-normalisation’; women and gender; cultural and intellectual currents; everyday life and popular opinion; and Czechoslovakia’s political and cultural relationship with the USSR, the GDR, Poland and Yugoslavia. The volume sheds light on the process of decay of the Czechoslovak communist regime and the reasons for its ultimate collapse in 1989. Kevin McDermott is Professor Emeritus of Modern East European History at Sheffield Hallam University. Matthew Stibbe is Professor of Modern European History at Sheffield Hallam University. They have jointly edited five previous volumes of essays on post-1945 Eastern Europe.